Magnetic order and Mott transition on the checkerboard lattice. (12th January 2017) - Swain, Nyayabanta; Majumdar, Pinaki
Abstract: The checkerboard lattice, with alternating 'crossed' plaquettes, serves as the two dimensional analog of the pyrochlore lattice. The corner sharing plaquette structure leads to a hugely degenerate ground state, and no magnetic order, for classical spins with short range antiferromagnetic interaction. For the half-filled Hubbard model on this structure, however, we find that the Mott insulating phase involves virtual electronic processes that generate longer range and multispin couplings. These couplings lift the degeneracy, selecting a 'flux like' state in the Mott insulator. Increasing temperature leads, strangely, to a sharp crossover from this state to a '120 degree' correlated state and then a paramagnet. Decrease in the Hubbard repulsion drives the system towards an insulator-metal transition—the moments reduce, and a spin disordered state wins over the flux state. Near the insulator-metal transition the electron system displays a pseudogap extending over a large temperature window.